P42 Disease activity, impaired iron transport and failed sequestration: a novel mechanism for anaemia in systemic lupus erythematosus. (23rd March 2020) - Wincup, Chris; McDonnell, Thomas; Robinson, George; Farinha, Filipa; Radziszewska, Anna; Isenberg, David; Rahman, Anisur
Abstract : Background: Haematological manifestations are a frequent feature of systemic lupus erythematosus (SLE) yet the role of abnormal iron metabolism is poorly understood. In this study, we investigated the role of key regulators of iron metabolism including ferritin (an iron carrier protein), transferrin (which facilitate iron transport to cell surface receptors), hepcidin (which prevents iron release from stores under the influence of IL6 and IL1β) and lipocalin-2 (LCN2, which is released by innate immune system activation and induces iron sequestration). Methods: Serum samples were collected from SLE patients without a history of haemolytic anaemia attending University College London Hospital, UK (n=39). Clinical parameters including Haemoglobin (Hb), dsDNA, complement C3 and SLEDAI-2K were recorded. Levels of IL1β, IL6, hepcidin, ferritin, LCN2 and transferrin in addition to other iron regulators including erythropoietin (EPO), soluble transferrin receptor (sTfR), haptoglobin (Hp) and NRAMP2, were measured by ELISA. Following normalisation of data, hierarchical correlate cluster was performed to produce a heatmap using MeV Software. Results: The results demonstrate a surprising negative correlation between LCN2 and SLEDAI-2K (P<0.001, r=-0.40), which suggests iron is not being appropriately sequestered in spite of immune activation. Hierarchical clustering is presented in figure 1 . Cluster analysis demonstrates that the group with the highest mean SLEDAI-2K (10.7) had lower Hb, transferrin and LCN2 in addition to elevated IL1β, IL6 and hepcidin compared with those with lower SLEDAI-2K. Elevated haptoglobin levels were seen in those in the higher disease activity groups, suggesting that haemolysis was an unlikely cause for anaemia. Conclusions: The findings of this study suggest increased lupus disease activity results in abnormal iron homeostasis through impaired cellular iron import (via reduced transferrin), a lack of stored iron release (under the actions of elevated hepcidin) and reduced iron sequestration by LCN2, which may represent a novel cause of non-haemolytic anaemia. Acknowledgements: This work was supported by Versus Arthritis (549143) and LUPUS UK (176255).